Tingkat Kepuasan Kelompok Pembudidaya Ikan (Pokdakan) Terhadap Kegiatan Penyuluhan Perikanan di Kabupaten Bandung, Jawa Barat - Shafa, Bellarisa Rahma; Gumilar, Iwang; Apriliani, Izza Mahdiana; Maulina, Ine (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cultivator satisfaction is an important thing in the implementation of fisheries extension activities. In this case, the satisfaction of cultivators is related to the quality of the fisheries extension services carried out. This study aims to analyze the level of satisfaction of cultivators with fisheries extension activities. The general research method used in this study is the case study method. The data collection technique in this study uses a selected sampling technique. The criteria used to determine respondents include active fish farmers for at least 1 year, continuous fish farming, and ready to be interviewed. The number of respondents interviewed was 61 people. The types of data collected include primary data and secondary data. Primary data was collected through interviews using questionnaires and field observations. Secondary data is obtained from related agencies and the results of research and scientific publications. The analysis method used is quantitative descriptive analysis. The parameter measured is the level of satisfaction of fish farmers using the Customer Satisfaction Index (CSI) method. The indicators used include tangible, responsiveness, reliability, assurance, and empathy. The results of the study indicate that the level of satisfaction of fish farmers is very satisfied, with an average CSI score of 83.36%. The average CSI value for tangible indicators was 4.36%, responsiveness was 4.69%, reliability was 4.76%, assurance was 5.53%, and empathy was 6.61%. From the CSI value, it can be seen that the tangible indicator has the lowest average CSI value. The low tangible is suspected to be due to the lack of facilities and infrastructure used by extension workers during fisheries extension activities. For this reason, it is necessary to make efforts from the central government in providing assistance to fisheries extension workers in Bandung Regency due to the lack of facilities and infrastructure to support in carrying out extension activities.